LAE Galaxies at High Redshift: Formation Sites for Low-Metal Globular Clusters. (5th March 2015) - Elmegreen, Bruce G.; Malhotra, Sangeeta; Rhoads, James
Abstract: Lyman-α emitting (LAE) galaxies observed at intermediate to high redshift have the correct size, mass, star formation rate, metallicity, and space density to have been the formation sites of metal-poor globular clusters. LAEs are typically small galaxies with transient starbursts. They should accrete onto spiral and elliptical galaxies over time, delivering metal-poor clusters into the larger galaxies' halos as they themselves get dispersed by tidal forces. The galaxy WLM is a good example of a dwarf remnant from a very early starburst that contains a metal-poor globular cluster but failed to get incorporated into the Milky Way or M31 because of its remote location in the local group.